자궁내막암의 단독 소장 전이로 인해 유발된 공장-공장 장중첩증: 증례 보고 - 장연; 박동희; 공준석; Yeon Jang; Dong Hee Park; Joon Seog Kong (Journal of the Korean Society of Radiology, 2022)
Endometrial carcinoma is a common gynecologic malignancy; however, metastasis to the small bowel is rare. Metastatic endometrial carcinoma usually occurs through local extension rather than distant metastasis. Isolated small bowel metastasis is extremely rare; further, intussusception with resultant intestinal obstruction is not common. We report the imaging findings of a patient with isolated small bowel metastasis of endometrial carcinoma with resultant jejunojejunal intussusception. 자궁내막암은 흔한 부인과암으로 소장으로의 전이는 드물며, 원격 전이보다 주변 장기로의 국소 침윤으로 발생한다. 자궁내막암이 다른 곳에 전이 소견 없이 단독으로 소장에 전이한 경우는 매우 드물다. 또한 성인에서 장중첩증은 드문 질환으로 이로 인해 장폐색이 발생하는 비율은 매우 낮다. 저자들은 자궁내막암 병기 IB로 수술 및 방사선 치료 후 경과관찰 중이던 환자에서 공장공장 장중첩증으로 인해 장폐색이 발생하였음을 소장 조영술 및 복부 전산화 단층촬영으로 진단하였고, 공장 국소절제술 후 자궁내막암의 단독 소장 전이로 확인하였던 증례를 문헌고찰과 함께 보고한다.